2017
DOI: 10.18632/oncotarget.18310
|View full text |Cite
|
Sign up to set email alerts
|

XIST/miR-139 axis regulates bleomycin (BLM)-induced extracellular matrix (ECM) and pulmonary fibrosis through β-catenin

Abstract: Pulmonary fibrosis (PF), characterized by the destruction of lung tissue architecture and the abnormal deposition of extracellular matrix (ECM) proteins, currently has no satisfactory treatment. In the present study, we investigated the hypothesis that XIST play a promotive role in bleomycin (BLM)-induced ECM and pulmonary fibrosis; XIST exerts its effect through miR-139 regulation. XIST expression was upregulated in lung tissues derived from BLM-induced mouse model of PF, and was positively correlated with β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Numerous studies have demonstrated that miRNAs are involved in the progression of diseases that occur in different tissues. For example, miR-139 was able to regulate pulmonary fibrosis via β-catenin (19). miR-122 has been demonstrated to be associated with iron overload-mediated hepatic inflammation (20).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that miRNAs are involved in the progression of diseases that occur in different tissues. For example, miR-139 was able to regulate pulmonary fibrosis via β-catenin (19). miR-122 has been demonstrated to be associated with iron overload-mediated hepatic inflammation (20).…”
Section: Discussionmentioning
confidence: 99%
“…The mice in the ALF model group were given intragastric administration with 4.8 g/(kg∙d) spirit, 24 mg/(kg∙d) pyrazole, 2 mL/(kg∙d) corn oil once daily for 12 weeks . Lentivirus targeting sh‐XIST (LV‐sh‐XIST) or the lentivirus negative control (LV‐sh‐NC) were dissolved in saline (10 mg/mL, 0.5 mL) and then injected into ALF model mice via tail vein for another 4 weeks . The sequence of LV‐sh‐XIST was 5′‐AUAACAGUAAGUCUGAUAGAGGACA‐3′.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, XIST is highly expressed in hepatocellular carcinoma tissues and promotes hepatocellular carcinoma progression . In addition, XIST was highly expressed in lung tissues from experimental pulmonary fibrosis (PF) model mice; and XIST knockdown attenuated mouse PF . However, the exact role of XIST in liver fibrosis remains undefined.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about miRNA functions in IPF; much of the functional data has been inferred from chemically induced mouse IPF models. In the lungs of mouse IPF models, miR-21, miR-9, and miR-155 were increased [19,21,30], and miR-26, miR-101, miR-139, miR-200, miR-326, miR-489, miR-503, and miR-708 were decreased [24,[31][32][33][34][35][36][37]. Furthermore, miR-21 expression was increased in myofibroblasts from IPF lungs, and its inhibition in mouse IPF models attenuated the disease severity [19].…”
Section: Ipf and Mirnasmentioning
confidence: 99%